Dialysis Adequacy among Haemodialysis Patients in Eastern Mediterranean Region: A Systematic Review and Meta-Analysis - Abbas Balouchi; Soroor Parvizy; Hamid Sharif Nia; Abbas Ebadi (ACHSM, 2021)
Introduction: Dialysis adequacy is one of the most important indicators for measuring the quality of care provided in hemodialysis (HD) wards. Despite individual studies, there is still no comprehensive study about dialysis adequacy in the Eastern Mediterranean Region (EMRO). This study was conducted to evaluate the dialysis adequacy in HD patients in the EMRO. Methods: In the present systematic review and meta-analysis international (EMBASE, Scopus, PubMed, Web of Science) and national (SID, MAGIRAN) databases were searched for related articles using keywords "dialysis adequacy" and "EMRO" from 1 January 2000 to April 30, 2020. The quality of studies was studied using Hoy et al instrument. Results: Out of 966 retrieved studies, 63 studies conducted on 15462 HD patients were included. The pooled mean of KT/V and URR were 1.24 (95% CI: 1.19, 1.30) and 63.03% (95% CI: 61.31, 64.75), respectively. The pooled prevalence of Kt/V>1.2 and URR>65.0% were 42.73% (95% CI: 31.58, 53.88) and 42.52% (95% CI: 25.3, 59.7), respectively. Conclusion: The results of the present study indicate the poor dialysis adequacy in the EMRO region and the need to improve the physical infrastructure, workforce, and pieces of equipment in hemodialysis wards.